AB1127 Health locus of control in systemic lupus erythematosus – a cross-sectional analysis of the lula-cohort in germany 2013. (15th June 2017) - Chehab, G; Richter, JG; Brinks, R; Fischer-Betz, R; Winkler-Rohlfing, B; Schneider, M
Abstract : Background: Health Locus of Control (HLC) is the degree to which individuals believe that their health is controlled by internal (self-responsibility) or external factors (healthcare professionals or chance). This generalized expectancy might affect different disease aspects, especially in chronic diseases. Objectives: Our objective was to assess the influence of HLC on different disease aspects in a representative sample of German systemic lupus erythematosus (SLE) patients. Methods: The LuLa-Study is a longitudinal survey on a multitude of SLE associated factors that is being conducted annually by means of a self-reported questionnaire among members of the German LE self-help community since 2001 and is ongoing. Inclusion criteria are a diagnosis of SLE and returning the completed paper questionnaire. Amongst others medication, health-related quality of life (Short-Form-12), damage (Brief index of lupus damage) and disease activity (Systemic Lupus Activity Questionnaire) are surveyed. In 2013 we additionally inquired about the health locus of control (HLC) that distinguishes between the "internal" HLCint (self-responsibility) and the two external dimensions HLCdoc and HLCchance considering their doctor respectively chance responsible for personal health. A high HLC was assumed for values above the upper quartile of the specific scales. Accessory questions examined fatigue (Fatigue severity scale), medication adherence (Morisky medication adherence scale), and illness perception (Brief illness perception questionnaire). Results: Patients with a high internal health locus of control (HLCint 13.1 vs. 9.1) had less pain (numeric rating scale 0–10), less flares, a better mental and physical health related quality of life, lower disease activity and less fatigue. Patients with a high external 'doctor'-related health locus of control (HLCdoc 10.7 vs. 7.2) were older, had more co-morbidities, more disease damage and received more frequently an immunosuppressive therapy. No significant differences were found between the patients with a high external 'chance'-related HLC compared to the lower scoring patients (HLCcha 11.1 vs. 6.3). Participants with a high external 'doctor'-related HLC had a more threatening view on their illness and a better adherence to medication (high adherence in 78.6% vs. 59.4%). Participants with a high internal HLC perceived their disease significantly less threatening. Higher education levels (school education, further education) went along with a decrease of external 'doctor'-related HLC (HLCdoc). Conclusions: Health locus of control has a significant impact in patients with SLE. Depending on the HLC different disease characteristics, treatments, levels of medication adherence and illness perception were noticed. Holistic care needs to consider the impact different HLCs may have. The direction of causality cannot be proved beyond reasonable doubt in this cross-sectional analysis. Hence additional longitudinal studies are necessary. Acknowledgements: The LuLa-study is supported by unrestricted grants from GlaxoSmithKline and UCB Pharma. Disclosure of Interest: G. Chehab Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study, J. Richter Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study, R. Brinks: None declared, R. Fischer-Betz Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study, B. Winkler-Rohlfing: None declared, M. Schneider Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study